Sprinting speed of elite sprinters at the world championships - Ryu, J.; Yoon, S.; Park, S. K.; Kim, T. S.; Gil, H.; Yoo, S. H.; Lee, G.; Koyama, H.; Mochida, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to analyze the sprinting speed of the sprinters during the men's 100 m events at the IAAF World Championships (WC) in order to provide important information to track and field coaches and athletes. Sprinting speed of the sprinters was collected by using laser guns (Laveg Sport, Jenoptik, Germany) during the World Championships in Daegu 2011. Then, data from Osaka 2007 WC and Berline 2009 WC were included in the analysis. The findings indicated that a reduction of a sprinter`s maximum speed is correlated with their performance time (p<0.05). Three top sprinters showed less than 2% reduction of thier maximum speed. Therefore, how the sprinters maintain their maximum speed until the end of the race is important for best performance.